Extraction of Total Dyestuff from Walnut Leaves (Juglans regia L.) and Its Dyeing Conditions for Natural Fibres - Onal, Adem; Camci, Nusret; Sari, Ahmet (Asian Journal of Chemistry, 2016)
The dyestuff of total dyestuff in walnut leaves (Juglans regia L.) was extracted by the reported method and used in dyeing of woollen strips, feathered-leather and cotton using three types of mordanting methods at various pH values. In order to determine the most proper mordant and pH value from the point of view of the wash, crock and light fastness in dyeing of the above samples by walnut, some selected transition element salts such as CuSO4·5H2O, FeSO4·7H2O, ZnSO4·7H2O, Al(NO3)3·9H2O were used as mordant agent at various pH. The experimental results indicate that dyed samples with the highest fastness were obtained by Cu(II) for the samples except for cotton and by Al(III) for only cotton at pH = 8 in the pre-mordanting method. The results also reveal that the wallnut plant containing juglone dyestuff will probably be an important raw material in the dyeing process of natural textile fibres.